Pemanfaatan LiMuKaSe Dalam Aromaterapi bagi Tubuh - Ammase Sufarman; Rita Tasmita; M. Irwan Ali; Nasra Wirdana; Nurfadella (Universitas Muhammadiyah Kolaka Utara, 2025)
Aromatherapy, utilizing three ingredients, shows significant potential in stress management. This study evaluated the effectiveness of LiMuKaSe aromatherapy candle, which innovatively combines eucalyptus, cinnamon, and lemongrass oils, in reducing stress. The aim of this study was to investigate the potential relationship and cooperation of the combination of these three ingredients. The method used was a qualitative approach, including a review of relevant scientific literature to evaluate the individual properties of each oil and their potential synergistic effects. The review results indicate that each of the ingredients (eucalyptus, cinnamon, and lemongrass oils) has therapeutic properties that support stress reduction, such as anti-inflammatory, analgesic, antioxidant, and calming effects. However, research on the effects of this combination of these three ingredients is still limited. In conclusion, LiMuKaSe has potential as an aromatherapy product for stress reduction, but further quantitative research is needed to validate the effects of this formulation and clearly and concretely measure its effectiveness in human populations.